2021
DOI: 10.1002/ange.202101388
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Biosupercapacitor Inspired by the Cellular Redox System

Abstract: The carbon nanotube (CNT) yarn supercapacitor has high potential for in vivo energy storage because it can be used in aqueous environments and stitched to inner parts of the body, such as blood vessels. The biocompatibility issue for frequently used pseudocapacitive materials, such as metal oxides, is controversial in the human body. Here, we report an implantable CNT yarn supercapacitor inspired by the cellular redox system. In all living cells, nicotinamide adenine dinucleotide (NAD) is a key redox biomolecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Without additional packaging, the specific capacitance of the CNT fiber supercapacitor reached 11.4 F/g and 13 F/g in serum and blood, respectively, as well as a stable specific capacitance after 10000 cycles in phosphate buffered saline (PBS). Jang et al [ 173 ] reported an implantable CNT yarn supercapacitor based on the redox system of Nicotinamide adenine dinucleotide (NAD) in living cells. The CNT yarn electrodes exhibited a maximum area capacitance (55.73 mF/cm 2 ) in PBS and serum, and a negligible loss of capacitance after 10000 repeated charge/discharge cycles and bending/knotting deformation.…”
Section: Conductive Fibers In Implantable Bioelectronicsmentioning
confidence: 99%
“…Without additional packaging, the specific capacitance of the CNT fiber supercapacitor reached 11.4 F/g and 13 F/g in serum and blood, respectively, as well as a stable specific capacitance after 10000 cycles in phosphate buffered saline (PBS). Jang et al [ 173 ] reported an implantable CNT yarn supercapacitor based on the redox system of Nicotinamide adenine dinucleotide (NAD) in living cells. The CNT yarn electrodes exhibited a maximum area capacitance (55.73 mF/cm 2 ) in PBS and serum, and a negligible loss of capacitance after 10000 repeated charge/discharge cycles and bending/knotting deformation.…”
Section: Conductive Fibers In Implantable Bioelectronicsmentioning
confidence: 99%
“…So far, there have been no reports on the use of biologically active ions such as neurotransmitters for the realization of switchable supercapacitors. Only few studies focus on the interaction of biologically active ions and porous carbon electrodes with and without electric polarization [12c,d, 13] . However, a deep understanding of electrosorption vs. physisorption mechanisms at the molecular level and the deliberate control of biologically active ion adsorption is essential for the rational design of neuromorphic interfaces and devices, neurotransmitter sensors, as well as new carriers for transmitter delivery [5–7] .…”
Section: Introductionmentioning
confidence: 99%